2015
DOI: 10.1016/j.clim.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A chimeric human–mouse model of Sjögren's syndrome

Abstract: Despite recent advances in the understanding of Sjögren's Syndrome (SjS), the pathogenic mechanisms remain elusive and an ideal model for early drug discovery is not yet available. To establish a humanized mouse model of SjS, peripheral blood mononuclear cells (PBMCs) from healthy volunteers or patients with SjS were transferred into immunodeficient NOD-scid IL-2rγ(null) mouse recipients to produce chimeric mice. While no difference was observed in the distribution of cells, chimeric mice transferred with PBMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…While these humanized mice gradually develop allogenic graft versus host disease, limiting their use for many therapy studies, the up-regulation of PD-1 during acute graft versus host disease made it possible to image the biodistribution of this immunotherapy target in our case (21). Similar to our findings, several research groups have reported that engrafted immune cells infiltrate the salivary glands and lacrimal glands in PBL mice (2224). Thus, we expected that the PD-1 expressing T cells would localize in the salivary glands in PBL mice, thus verifying that our PD-1 tracer was effective for imaging of PD-1-expressing T cells in vivo .…”
Section: Discussionsupporting
confidence: 92%
“…While these humanized mice gradually develop allogenic graft versus host disease, limiting their use for many therapy studies, the up-regulation of PD-1 during acute graft versus host disease made it possible to image the biodistribution of this immunotherapy target in our case (21). Similar to our findings, several research groups have reported that engrafted immune cells infiltrate the salivary glands and lacrimal glands in PBL mice (2224). Thus, we expected that the PD-1 expressing T cells would localize in the salivary glands in PBL mice, thus verifying that our PD-1 tracer was effective for imaging of PD-1-expressing T cells in vivo .…”
Section: Discussionsupporting
confidence: 92%
“…Histological analysis showed signs of inflammation within the lacrimal and salivary glands of mice engrafted with SjS. These infiltrates were mostly CD4 + and a small population of CD8 + T cells and B cellsYoung et al (2015)Type I diabetesNSG-Ab o  DR4 engrafted with CD4 + T cells pulsed with autoantigen-derived peptidesMice injected with autoantigen-reactive CD4 + T cells lines from diabetic donors demonstrated human T cells infiltration into mouse islets, insulitis, and increased levels of demethylated β-cell–derived DNA in the bloodstream and reduced levels of insulin stainingViehmann Milam et al (2014) SLE Systemic lupus erythematosus, SjS Sjogren’s syndrome, CNS central nervous system …”
Section: Models Of Human Diseases Established On Humanized Micementioning
confidence: 99%
“…In addition, these investigators observed the infiltration of significantly larger numbers of human CD4 + T cells into the salivary and lacriminal glands of the SS- vs HD-engrafted NSG mice. Although significantly larger numbers of human CD8 + T cells and B cells were observed in both glands in SS- vs. HD-engrafted animals, the absolute numbers of these lymphocytes were much smaller than those observed for CD4 + T cells (200). This inflammatory infiltrate correlated well with loss of target organ function as saliva production was significantly decreased by 36% at 4 weeks post transfer of SS-derived PBMCs.…”
Section: Use Of Humanized Mice To Study Autoimmune and Inflammatory Dmentioning
confidence: 67%
“…Because the pathology observed in these mouse models of SS do not reproduce some of the key alterations described in human disease, investigators are just beginning to explore the use of humanized mice to study the immuno-pathological mechanisms responsible for induction of this prevalent disease. In the first and only study reporting the use of humanized mice in SS investigations, Andrade and coworkers showed that adoptive transfer PBMCs obtained from SS donors into NSG mice resulted in increased serum levels of a variety of human inflammatory cytokines including IFN-γ, IL-17, Il-6 and TNFα when compared to NSG engrafted with healthy donor (HD) PBMCs (200). In addition, these investigators observed the infiltration of significantly larger numbers of human CD4 + T cells into the salivary and lacriminal glands of the SS- vs HD-engrafted NSG mice.…”
Section: Use Of Humanized Mice To Study Autoimmune and Inflammatory Dmentioning
confidence: 99%